EFFECT OF ZEOLITE ON EFFICIENCY OF P AND K FERTILIZERS IN THE PADDY FIELD - Abdulrachman, Sarlan; Susanti, Zuziana (Jurnal Zeolit Indonesia, 2004)
Zeolite generally have a very high exchange ion capacity and capability to catch ions. Therefore, zeolite is used on agriculture to reduce ion movement around the root zone and to increase the use of fertilizer by plant. A research have been established on 1999/2000 using zeolite from two sites that represent two type of soil, Planosol soil from Jakenan (Pati) and Podsolic soil from Tamanbogo (Lampung).Group randomize design with three repetition is used on this research. Fertilizer treatment on this research are 60-100 % P or K and 0-40% zeolite, 100% P or K + 200- 300% kg/ha zeolite. The final result of this research showed that in order to produce high quality of paddy on podsolic soil need the P fertilizer. The zeolite been given along with P fertilizer worth while to increases efficiency, even though it did not positively increasing yield. Adding 300 kg/ha zeolite can reduce the use of fertilizer around 20% P. The Same thing happened to fertilizer K on planosol. Zeolite plus which enriched by a number of minerals giving a better result compare to the one without enrichment. On greenhouse atmosphere, though dosage of zeolite plus (5-10 t/ha) used to increase exchange ion capacity on soil, producing rice around 11.9 t/ha. But on the field, the production decreases cause by heavier disease attack due to the too crowded plantation and too damp condition around the canopy. This is why it is necessary to give the right zeolite plus dosage, not just to increases efficiency, but also to make it financially reachable by the farmer.